Recent Progress in Electrocatalytic Conversion of Lignin: From Monomers, Dimers, to Raw Lignin - Liu, Xiang; Wang, Ye; Duan, Haohong (Precision Chemistry, 2024)
Lignin, as the second largest renewable biomass resource in nature, has increasingly received significant interest for its potential to be transformed into valuable chemicals, potentially contributing to carbon neutrality. Among different approaches, renewable electricity-driven biomass conversion holds great promise to substitute a petroleum resource-driven one, owing to its characteristics of environmental friendliness, high energy efficiency, and tunable reactivity. The challenges lie on the polymeric structure and complex functional groups in lignin, requiring the development of efficient electrocatalysts for lignin valorization with enhanced activity and selectivity toward targeted chemicals. In this Review, we focus on the advancement of electrocatalytic valorization of lignin, from monomers, to dimers and to raw lignin, toward various value-added chemicals, with emphasis on catalyst design, reaction innovation, and mechanistic study. The general strategies for catalyst design are also summarized, offering insights into enhancing the activity and selectivity. Finally, challenges and perspectives for the electrocatalytic conversion of lignin are proposed.